One theorem on the rate of convergence in the central limit theorem - Paulauskas, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Паулаускас. Одна теорема о скорости сходимости в центральной предельной теореме V. Paulauskas. Viena teorema apie konvergavimo greitį centrinėje ribinėje teoremoje